Commentary on the judgment of the Supreme Court, from July 20, 2020. Denial of spanish nationality of origin to those born in former Equatorial Guinea. - Castelucci Paoloni, Olga Beatriz (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
This article analyzes the Judgment of the Supreme Court from July 20, 2020, which denies the Spanish nationality of origin to the plaintiff born in Spain whose parents were born in Equatorial Guinea, before the declaration of independence and when they were still territories under Spanish rule. The legal status of the territories of Guinea, Ifni and Western Sahara is raised during the stage as a Spanish colony, and if they are Spain for the purpose of acquiring nationality based on the ius soli. To the application of specific regulations and in the same way as with respect to Western Sahara. The succession of States in the case of the Republic of Equatorial Guinea as differentiating element.